Swot Analysis Based on Total Quality Environmental Management: Case Study at PT. Yanaprima Hastapersada, Tbk. - Lira Mustika Sari; Ratna Asri Solihati; Popy Rufaidah (Journal of International Conference Proceedings (JICP), 2018)
Environmental damage is a problem faced by the world globally due to environmental pollution from processing industrial production activities. Pollution can arise due to the negligence of the company in fulfilling its obligations and responsibilities towards the surrounding environment. This should be a concern for companies to participate in and be responsible for the company's external environment (ecology). Therefore, this study aims to identify the implementation of environmental strategies carried out by PT. Yanaprima Hastapersada, Tbk. The study used case study in exploring firm’s related practices of the four-element of Total Quality Environmental Management (TQEM). The SWOT analysis shows that the strength of the company come from the differentiation of its products offered to its target market; the brand reputation that became the identity of its product and company; the service quality to maintain the repeat orders from its customers; and the distribution channels to reach wider consumers in various locations. The study shows that the firm has applied the four-element of TQEM. These are: the use of machinery that is able to increase environmentally friendly productivity, the maintaintenance of the environmental's production, the application of the business ethics in the company, the development of waste storage, and the treatment of the waste that still has economic value.